EVALUATION OF CHARACTER EDUCATION PROGRAM ON IMPROVING STUDENTS' CHARACTER AT SMPK BPK PENABUR BANDUNG - Heriyanto; Achmad Kurniady, Dedy; Nurdin (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to evaluate the character education program in improving student character at SMPK BPK Penabur Bandung. Character education is an important aspect in shaping students' positive personality and behavior. SMPK BPK PENABUR Bandung, as one of the leading schools, has implemented a character education program, but there has been no comprehensive evaluation of its effectiveness. This study was conducted to evaluate the character education program at SMPK BPK PENABUR Bandung in improving student character, so that it can provide valuable insights for the development of similar programs in the future. This study uses a qualitative approach to gain an in- depth understanding of the implementation and impact of the character education program at the school. Data were collected through in-depth interviews with teachers, students and school administrators, direct observation of character education activities and analysis of related documents. The focus of the research includes the planning, implementation and evaluation processes of the program, as well as the observed changes in student character. The results show that SMPK BPK Penabur Bandung has implemented a character education program systematically and integrated in the curriculum. The program includes various activities such as learning character values in subjects, mentoring programs, character-based extracurricular activities, and parental involvement. Key findings indicate significant improvements in aspects of student character, including honesty, responsibility, discipline and social care. However, some challenges were also identified, such as consistency in the application of character values outside the school environment and differences in perceptions between schools and parents regarding character education methods. This study concludes that the character education program at SMPK BPK Penabur Bandung is effective in improving students' character, although there is still room for improvement. Recommendations include increasing collaboration with parents, developing more comprehensive character evaluation methods, and strengthening the integration of character values in students' daily lives outside of school.